HEGEMONI KIAI TERHADAP DEMOKRATISASI DI PESANTREN:: Analisis Bahasa Tutur Pengasuh PP Raudlatul Ulum 2 Putukrejo Gondanglegi Malang - Muhammad Madarik; Hairul Puadi (LP3M IAI Al-Qolam, 2019)
This research tries to uncover kiai's hegemony based on the perspective of language which is correlated with the discourse of democratic values. Gramsci's hegemony is used as the basis for analyzing word structures in the context of the territory of a pesantren caregiver, to dissect the level of kiai's intervention on the sustainability of democratization through his utterances. The context of power uses Foucault's assertion, that the pattern of power relations cannot be conceptualized as belonging to an individual or class. Therefore, the author tries to distill the level of democracy from the power relations of the kiai at pesantren Raudlatu Ulum 2 Putukrejo Gondanglegi Malang through the texture perspective of his expressions. The method used is Qualitative research. This type of research uses methods of observation, interviews and documentation. In analyzing the data, the researcher uses the following steps: Field notes are reduced in categories. The results are presented for each category. Analysis of the language of caregivers in this paper is limited to two aspects: First, things that are nuanced politically. Second, matters relating to policies within the scope of pesantren.